The journey of lithium ions in the lattice of PNb9O25. (8th January 2020) - Yu, Haoxiang; Zhang, Jundong; Zheng, Runtian; Liu, Tingting; Peng, Na; Yuan, Yu; Liu, Yufei; Shu, Jie; Wang, Zhen-Bo
Abstract : Evidence for the movement of inserted lithium ions in the insertion host PNb9 O25 is provided according to the variation for reflection intensities. Abstract : The investigation of the lithiation mechanism for anode materials plays a key role in the field of lithium-ion batteries. It can always offer a new approach to design and develop anode materials to improve their electrochemical performance. Therefore, we have studied the lithiation mechanism of PNb9 O25 during cycling by the adoption of the in situ X-ray diffraction technique coupled with the analysis of a structure model in this work. The results present that PNb9 O25 reacts with lithium at 1.62 and 1.11 V with a small lattice volume expansion of 10.69%. Meanwhile, based on the evolutions of the selected reflections ((130), (141), and (370)), the position of the inserted lithium ions in the lattice is revealed and thus, the diffusion channels of lithium ions can be inferred from it. According to this lithiation mechanism, we can find out some new avenues to design and develop the morphology of PNb9 O25 or other niobate materials.